First BVR light curves and preliminary results of a recently discovered W UMa-type binary: V1848 Ori - W. Kriwattanawong (2018)
First complete photometric light curves of a recently discovered contact binary, V1848 Ori, are presented. BVR imaging data were used to derive photometric solutions, using Wilson-Devinney code. We discovered that this system is a weak-contact binary, with a fillout factor of f = 13.14%(±1.44%). Preliminary results showed that V1848 Ori is an A-type W UMa system, with a mass ratio of q = 0.7615. The more massive component was found about 400 K hotter than the other one. This system has varied from W-type to A-type during the last decade. According to the preliminary physical parameters, the weak-contact configuration of this system, with the mass ratio close to unity, and no sign of long-term orbital period change yet, is unlikely to be broken. The contact configuration is expected to be maintained and become deeper or not, depending on effect of the AML mechanism. © 2013 Elsevier B.V. All rights reserved.